Review of South African Euryphyminae - Tshililo, Precious (Zootaxa, 2020)
Euryphyminae is a Southern African endemic subfamily, which to date consists of 23 genera. We collected all available information from historic literature accounts, 626 positively identified museum specimens from 16 genera and 624 fresh field-collected specimens from eight genera to review the Euryphyminae genera of South Africa. Three genera are recorded for the first time to occur in South Africa; Rhodesiana Dirsh, 1959, Acrophymus Uvarov, 1922 and Plegmapteropsis Dirsh, 1956, while Aneuryphymus rhodesianus species is also recorded for the first time in South Africa. This brings the total number of genera occurring in South Africa from 14 to 16 genera of Euryphyminae. Finally, distribution maps for each genus are provided along with an updated key to genera.